Periodontal pathogens of the interdental microbiota in a 3 months pregnant population with an intact periodontium - Carrouel, Florence; Kanoute, Aida; Lvovschi, Virginie-Eve; Bourgeois, Denis (Frontiers in Microbiology, 2023)
Steroid hormones and the oral microbiota of pregnant women both appear as cumulative risk factors for gingivitis. This cross-sectional study, using real-time PCR, investigated the composition and diversity of the microbiota in interdental spaces of 3-month pregnant women with intact periodontium according the 2018 EFP/AAP classification. Bacteria identified were belonged to the red (Porphyromonas gingivalis Treponema denticola and Tanerella forsythia), orange (Fusobacterium nucleatum, Prevotella intermedia, Campylobacter rectus and Parvimonas micra) and green (Eikenella corrodens and A. actinomycetencomitans) Socransky complexes. Approximatively 10 9.11 bacteria were counted per interdental space in pregnant women. Bacteria from the red complex represented 33.80% versus 62.81% for the orange group versus 3.39% for the green group of the total number spread over the 3 groups. Dietary habits and physical activity did not have a significant impact on interdental microbiota, although a decrease in the median amount of 9 periodontopathogens was observed when fruit and vegetable consumption increased. Pregnant women who brushed their teeth at least twice a day had lower counts of total bacteria and 9 periodontal pathogens than those who brushed less. In 3-month pregnant women at high risk of periodontal disease (>30% bleeding sites), the dendogram revealed 2 clusters of the 9 periodontopathogens. This provides further support for the "key pathogen" hypothesis, among which Porphyromonas gingivalis plays a key role, indicating that specific bacteria in limited quantities can influence the host immune system and convert the microbiota from symbiotic to dysbiotic to induce inflammatory disorder. As a result, this study reported that 3-month pregnant women with healthy This is a provisional file, not the final typeset article periodontium had high levels of interdental bleeding and a dysbiotic microbiota with periodontal pathogens of the Socransky orange and red complexes. These subjects were therefore potentially at increased risk of developing periodontal disease and, consequently, an adverse pregnancy outcome. So, preventive oral prophylaxis measures, in particular individual interdental prophylaxis, should be implemented as soon as pregnancy is established.